New metal complexes of sulfonamide: Synthesis, characterization, in‐vitro anticancer, anticholinesterase, antioxidant, and antibacterial studies. (15th October 2020) - Danish, Muhammad; Raza, Muhammad Asam; Khalid, Hirra; Iftikhar, Umara; Arshad, Muhammad Nadeem
Abstract : In this research work a sulfonamide from tranexamic acid has been synthesized followed by its metal complexation. p ‐Bromo benzene sulfonyl chloride was used to synthesize sulfonamide using eco‐friendly atmosphere. The sulfonamide prepared from tranexamic acid has been utilized for the preparation of metal complexes with various metals like Ni, Cu, Co, Mn, Pb, Cd, Cr, Fe, Sn, and Sr. All synthesized compounds were characterized by applying different spectral techniques such as Fourier‐transform infrared (FTIR), mass spectrometry, and X‐ray diffraction (XRD) analysis. The biological activities such as radical scavenging activity, enzyme inhibition, antifungal, antibacterial, and anticancer were performed. It was concluded from the results that compounds showed moderate to good activity. Cu complex of sulfonamide showed the highest antioxidant potential (87.69 ± 1.8% with IC50 137 ± 1.0 μg) while Cr complex depicted the highest activity against both enzymes; AChE (73.51 ± 1.7% with IC50 165 ± 1.1 μg) and BChE (70.05 ± 1.3% with IC50 152 ± 1.8 μg). Mn complex showed good results against six bacterial strains comparable with standard drug. Cr complex depicted highest anticancer activity against MCF7 and human corneal epithelial cell (HCEC) cell lines 45.73% and 25.40%, respectively. These results concluded that metal complexes of sulfonamide may be good induction in the future for medical purposes. Abstract : Our research group is continuously working on synthesizing of new ligands and their metal complexes having great biological interest. This work is also a continuity of that effort; here, we synthesized new sulfonamide from cheaper source and under green atmosphere. Nine metal complexes have been prepared, and their structures were elucidated with FTIR, mass spectrophotometry, and single‐crystal XRD analysis. The metal complexes exhibited good antioxidant, enzyme inhibition (AChE and BChE), anticancer (MCF7 and HCEC), and antibacterial (six bacterial strains) potential.